146k views
0 votes
Use mathematical induction to prove that if a ∈ ℝ and r≠1then a+ar^1+ar^2+...+ar^(n+1)=a(r^n+1)/(r-1).

User Kiriloff
by
5.3k points

1 Answer

4 votes

Answer:

Explanation:

In this problem we are proving the equality


a + ar + ar^2 +\cdots + ar^n = a(1-r^(n+1))/(1-r).

When we want prove an equality by induction we need to follow some steps.

First: Check the hypothesis for some initial cases. In this exercise we take


n=0: we have
a = a(1-r)/(1-r) = 1. So the equality holds for
n=0.


n=1: we have
a + ar =a(1+r)= a(1-r^2)/(1-r) = a((1-r)(1+r))/(1-r) = a(1+r). So the equality holds for
n=1.

After we have checked the hypothesis for
n=0,1 can continue to the next step.

Second: State the induction hypothesis for
n=k. In this case the hypothesis is:


a + ar + ar^2 +\cdots + ar^k = a(1-r^(k+1))/(1-r).

Now, it comes the last step and, usually, the most difficult.

Third: Prove the statement for
n=k+1 (using that the equality holds for
n=k!). This means that we want to prove that:


a + ar + ar^2 +\cdots + ar^k + ar^(k+1) = a(1-r^(k+2))/(1-r).

So, let us start by the left hand side and try to get the left hand side.


a + ar + ar^2 +\cdots + ar^k + ar^(k+1).

We can group the above sum in the following way


a + ar + ar^2 +\cdots + ar^k + ar^(k+1) =(a + ar + ar^2 +\cdots + ar^k) + ar^(k+1).

Notice that the expression under parenthesis is the same we have in our induction hypothesis. Then,


(a + ar + ar^2 +\cdots + ar^k) + ar^(k+1) = a(1-r^(k+1))/(1-r) + ar^(k+1).

Now, we operate the sum that appears in the right hand side:


a(1-r^(k+1))/(1-r) + ar^(k+1) = (a - ar^(k+1)+ar^(k+1)-ar^(k+2))/(1-r) = (a-ar^(k+2))/(1-r) = a(1-r^(k+2))/(1-r).

So, we have obtained that


a + ar + ar^2 +\cdots + ar^k + ar^(k+1) = a(1-r^(k+2))/(1-r),

which is exactly what we want to prove.

User Mppl
by
5.2k points